The study of inventory waste management in micro scale food industry in Bandung, case study bola ubi Yama - Mangku Alam, Asnawi; Farmaciawaty, Desy Anisya (Journal of Innovation, Business and Entrepreneurship, 2020)
Management constraints are often experienced by micro businesses in the culinary industry. Limited resources and poor management lead to many losses. Yama, one of the micro companies engaged in culinary, experienced obstacles in overcoming and managing the remaining inventory. Its possible that leftovers are often become problem that needs attention in running a culinary business. This research aims to learn how the micro-business conditions in the culinary industry in Bandung in dealing with the problem of remaining inventory or inventory waste. This research also aims to find suitable methods to overcome these problems and look for possible impacts that will occur after applying appropriate management methods. To find out the condition of micro-business is resolved by doing interviews using a qualitative approach, then the data is processed by coding methods. Interviews were conducted with four respondents who involved micro-scale culinary businesses in Bandung. In selecting the appropriate method, this research uses a rubric by comparing the criteria of the methods found with the characteristics of Yama's products and companies as the study model in this research. In determining the method, a literature review is also carried out first. To test and find possible impacts that occur, this research uses secondary data from Yama to be used as a calculation model. The results of interviews and coding found that the micro business condition in the culinary industry currently has a running management based on intuition without any scientific approach, supported by other factors, it is concluded that waste inventory management becomes an important topic. The method chosen by matching the characteristics is the single period inventory method, because the method has a match with Yama's system and problems in order to reduce the amount of inventory waste. The results of the calculation model show that the single period inventory method has a positive impact, such as increasing Yama's opportunity to make a profit and decreasing the possibility of inventory waste due to unsold inventory.